Comparative analysis of the concessioning model of maritime domains in the territory of both the European Union and the Republic of Croatia with a focus on the seaports - Mišura, Antonija (Array, 2020)
The maritime domain is the common domain of special interest, so it has special protection of the state and certain rules of use. One of the models of the maritime domains management in the territory of the Republic of Croatia is the concessioning system, and it is based on various legislation and by-laws that determine the type of concessions, the method of determining the concession fee and the methods and criteria for awarding the concession. The concessions’ management is primarily related to the economic use of maritime domains. The aim of this article is to carry out a comparative analysis of the concessioning model of maritime domains in the territory of the Republic of Croatia and the European Union with a focus on the seaports. For the purpose of economic use, today’s models of the maritime domains’ concessioning in the territory of the European Union are not unambiguous, as they depend on the tradition and historical development of the system even though they are subject to constant changes. The carried out research points to the need of developing the system in the Republic of Croatia with the obligation to harmonising legislation, strengthening criteria within the system and increasing the degree of openness of the market in accordance with the European acquis.